Molecular phylogeny of social vespid wasps inferred from DNA sequence of 28s and Coi gene / Muhamad Arif Mohamad Jamali - Mohamad Jamali, Muhamad Arif (2015)
Social wasps (Vespidae) display a wide range of diversity in their ecology and social organisation, providing insights imo thc origins of simple societies and the elaboration and maintenance of complex societies Cladistic analysis of behavioral data showed that Stenogastrinae have been grouped with social Polistinae and Vespinae in the family of Vespidae‘ However, it has been reported that Stenogaslrinae are more closely related to the solitary wasps Eumeninac than other social subfamilies, based on their morphological characters. The aim of this study was to determine the relationship between the subfamilies in the social vespid wasps (Stenogastrinae, Polistinae, and Vespinae) based on CO! mitochondrial DNA and 28S ribosomal nuclear DNA. A total number of 18 species of eight genuses within the three subfamilies of Vespinae, Polistinae and Stenogastrinae, were successfully collected throughom Peninsular Malaysia. Five individuals from each species were selected for genomic DNA extraction, PCR amplification and sequencing Phylogenetic analyses were conducted using Neighbor-Joining (NJ) and Maximum Parsimony (MP) methods that performed using the computer program MEGA 6‘ Six topology of the phylogenetic tree were generated. Comparison of both topologies of phylogenetic trees showed that 288 gave better resolution at higher taxa level while C01 region resolved better at the lower Iaxa or species level compared with the higher taxa. The combined locus gave best phylogenetic tree because it carried both properties locus in the topology ofthe tree, NJ tree of combined locus (285 and C01) portrayed the best result to understand the relationship between these subfamilies‘ The topology shows that subfamily Stcnogastrinae were the first to diverge from the outgroup‘ Then this followed by subfamily Vespinae and subfamily Polistinae, Subfamily Vespinae formed a monophyletic clade with the subfamily Polistinae while Stenogastrinae was placed as the sister clade from other two social wasps.